Antiganglioside Antibodies and Inflammatory Response in Cutaneous Melanoma. (13th August 2020) - Ene, Corina Daniela; Tampa, Mircea; Nicolae, Ilinca; Mitran, Cristina Iulia; Mitran, Madalina Irina; Matei, Clara; Caruntu, Ana; Caruntu, Constantin; Georgescu, Simona Roxana
Abstract : Introduction . Endogenously produced antiganglioside antibodies could affect the evolution of cutaneous melanoma. Epidemiological and experimental evidence suggest "chronic inflammation" to be one of the hallmarks in skin cancers. The aim of the study was to characterize the relation between antiganglioside antibodies and inflammation in cutaneous melanoma focusing on gangliosides GM1, GM2, GM3, GD1a, GD1b, GT1b, GQ1b. Material and Method . We performed an observational study that included 380 subjects subdivided into three groups: patients with metastatic melanoma (170 cases), patients with primary melanoma (160 cases), and healthy subjects (50 subjects). The assessment of antiganglioside antibodies, IgG, and IgM classes, against -GM1, -GM2, -GM3, -GD1a, -GD1b, -GT1b, -GQ1b was performed using immunoblot technique (EUROLine kit). Results . The presence of IgG and IgM antiganglioside antibodies in primary melanoma was (%), as follows: anti-GM1 (5.0 and 13.1), -GM2 (1.8 and 18.1), -GM3 (0.6 and 5.6), -GD1a (0.6 and 15.0), -GD1b (3.7 and 10.7), -GT1b (0.0 and 13.1), -GQ1b (0.0 and 5.0). In metastatic melanoma, the level of antiganglioside antibodies was significantly lower compared with primary melanoma (p < 0.05 ), while in the control group they were absent. Antiganglioside antibodies anti-GM1 and -GD1a were positively correlated, while anti-GM3, -GD1b, and -GT1b were negatively associated with the inflammatory markers, interleukin 8 (IL-8), and C reactive protein (CRP). Conclusions . Tumour ganglioside antigens generate an immune response in patients with primary melanomas. The host's ability to elaborate an early antiganglioside response could be considered as a defence mechanism, directed toward eliminating a danger signal from the tumour microenvironment. Antiganglioside antibodies associated with inflammation markers could be used as diagnostic, monitoring, and treatment tools in patients with cutaneous melanoma.